Curaxin CBL0137 inhibits endothelial inflammation and atherogenesis via suppression of the Src‐YAP signalling axis. (29th December 2022) - Ding, Huanyu; Jiang, Minchun; Lau, Chi Wai; Luo, Jianfang; Chan, Andrew M.; Wang, Li; Huang, Yu
Abstract : Background and Purpose: Atherosclerotic vascular disease is the leading cause of mortality and morbidity worldwide. Our previous study uncovered that endothelium‐specific knockdown of YAP suppresses atherogenesis, suggesting that YAP is a promising therapeutic target against atherosclerotic vascular disease. We established a drug screening platform, which aimed to identify new YAP inhibitors for anti‐atherosclerotic treatment. Experimental Approach: Drug screening was performed by a luciferase reporter gene assay. RNA sequencing was performed to acquire the transcriptomic profile of CBL0137‐treated endothelial cells. We assessed and validated the inhibitory effect of CBL0137 on YAP activity and inflammatory response in HUVECs and HAECs. We evaluated the vasoprotective effect of CBL0137 in vivo against plaque formation in ApoE −/− mice, using both disturbed flow‐induced and chronic western diet‐induced atherosclerotic models. Key Results: We identified CBL0137 as a novel YAP inhibitor from an FDA drug library. CBL0137 inhibited YAP activity by restraining its phosphorylation at Y357. CBL0137 inhibited YAP activity to repress endothelial inflammation. Mechanistically, CBL0137 suppressed YAP phosphorylation at Y357 via the tyrosine‐protein kinase Src. Furthermore, administration of CBL0137 ameliorated endothelial inflammation and the atherogenesis induced by disturbed flow and consumption of an atherogenic diet in ApoE −/− mice. Conclusion and Implications: To our knowledge, this is the first study to identify CBL0137 as a novel YAP inhibitor. We have demonstrated that pharmacologically targeting YAP by CBL0137 inhibits atherogenesis. The present results suggest that CBL0137 holds promise as a new drug for the treatment of atherosclerotic vascular disease.